Genetic Engineering in Combination with Semi‐Synthesis Leads to a New Route for Gram‐Scale Production of the Immunosuppressive Natural Product Brasilicardin A. (1st May 2021) - Botas, Alma; Eitel, Michael; Schwarz, Paul N.; Buchmann, Anina; Costales, Paula; Núñez, Luz Elena; Cortés, Jesús; Morís, Francisco; Krawiec, Michał; Wolański, Marcin; Gust, Bertolt; Rodriguez, Mirna; et al.
Abstract: Brasilicardin A (1 ) consists of an unusual anti / syn / anti ‐perhydrophenanthrene skeleton with a carbohydrate side chain and an amino acid moiety. It exhibits potent immunosuppressive activity, yet its mode of action differs from standard drugs that are currently in use. Further pre‐clinical evaluation of this promising, biologically active natural product is hampered by restricted access to the ready material, as its synthesis requires both a low‐yielding fermentation process using a pathogenic organism and an elaborate, multi‐step total synthesis. Our semi‐synthetic approach included a) the heterologous expression of the brasilicardin A gene cluster in different non‐pathogenic bacterial strains producing brasilicardin A aglycone (5 ) in excellent yield and b) the chemical transformation of the aglycone 5 into the trifluoroacetic acid salt of brasilicardin A (1 a ) via a short and straightforward five‐steps synthetic route. Additionally, we report the first preclinical data for brasilicardin A. Abstract : The development of a heterologous producer strain that enables the sustainable production of the stereochemically complex natural products brasilicardin C and E at excellent rates is presented. The semi‐synthetic approach allows an efficient gram‐scale conversion of brasilicardin E into the potent immunosuppressant brasilicardin A for which the first preclinical data are reported.